Study and numerical simulation of photovoltaic cells based on chalcostibite materials - HMAITICHE, Abdelkrim; DJOUBER, Sif edin; Enca/ BENNACER, Hamza (university of M'sila, 2022)
In this work, by using the wxAMPS-1D package, we have studied and performed a simulation for a thin film solar cell based on Chalcostibite materials (CuSbS2 or CuSbSe2 adopted as an absorber layer), the first proposed solar cell is ZnO/CdS/ CuSbSe2 and the second is ZnO/CdS/ CuSbS2. We have optimized the layers thicknesses and doping concentrations in order to improve the photovoltaic performance of these solar cells, the obtained maximum efficiencies are 14.19 % and 18.84 %, for CuSbSe2 and CuSbS2 based solar cells, respectively.
Keywords: solar cells, Chalcostibite, CuSbS2, CuSbSe2, simulation, wxAMPS-1D.